Storing solar energy within Ag-Paraffin@Halloysite microspheres as a novel self-heating catalyst. (15th July 2018) - Zhao, Yafei; Kong, Weixiao; Jin, Zunlong; Fu, Ye; Wang, Wencai; Zhang, Yatao; Liu, Jindun; Zhang, Bing
Graphical abstract: Highlights: A novel self-heating catalyst Ag-Paraffin@Halloysite microsphere was prepared. Ag-Paraffin@Halloysite exhibits excellent heat storage/release capacity. It shows faster transient thermal response compared with paraffin. It displays much better catalytic activity after heat storage. This work may open up a new avenue of utilization of solar energy. Abstract: With the rapid depletion of fossil fuels and the associated environmental issues, solar energy is identified as one of the most promising pollution-free and renewable resource. Herein, we prepared a novel Ag-Paraffin@Halloysite microsphere with the integrated abilities of storing solar energy and catalytic function by self-assembly method. The results show that Ag-Paraffin@Halloysite microsphere has a core-shell structure with paraffin as core and halloysite as shell, and Ag nanoparticles are dispersed uniformly on the surface of the microspheres. The high thermal storage capability, encapsulation ratio and encapsulation efficiency of Ag-Paraffin@Halloysite indicate that it can be used as an ideal heat storage material. Compared with pure paraffin, Ag-Paraffin@Halloysite has higher thermal conductivity, excellent thermal storage capacity, and faster transient thermal response. After heat storage, Ag-Paraffin@Halloysite shows much better catalytic activity (95.3% of conversion in 6 min) compared with the one without heat storage (71.1% of conversion in 6 min) for catalytic reduction of 4-nitrophenol. This result suggests its potential to be used as a self-heating catalyst for storing/releasing thermal energy during catalytic reactions. This work may offer a general and innovative approach to couple phase change materials with catalyst and open up a new avenue for utilization of solar energy in the fields of chemistry and chemical engineering.